Factors contributing to poor adherence to a fixed dose combination treatment among patients living with Human Immunodeficiency Virus at HC Boshoff Community Health Centre in Sekhukhune District, Limpopo Province - Matlala, Malebeleko Jane (My University, 2023)
The South African Department of Health introduced the use of Fixed Dose Combination antiretroviral regimens to adhere to treatment in 2012, which reduce drug toxicity, keep patients on life-long ART, prevent the progression of HIV disease and prevent HIV/AIDS-related death. Since the introduction of Fixed Dose Combination (FDC), it has become the cornerstone in the treatment of HIV. FDCs' fundamental benefit is that they simplify a patient's regimen. When compared to the individual components, the usage of FDCs has been associated with reduced pill load and improved adherence. RESEARCH METHOD In this study, a qualitative research approach was used. This approach was considered to be appropriate and relevant in this study as the researcher was intended to describe factors contributing to poor adherence to a fixed-dose combination treatment among patients living with HIV at HC Boshoff CHC in Sekhukhune District, Limpopo Province. Data was collected through semi-structured face-to-face interviews and was analysed using open coding where themes and sub-themes were developed. RESULTS The study revealed that there are several factors that contributes to poor adherence to HIV positive patients who are on FDC, they are divided into 6 themes and 14 subthemes. Strategies were developed to improve adherence to a fixed-dose combination treatment among patients living with HIV. CONCLUSION The study concluded that patient has several factors that hinder their adherence to FDC at HC Boshoff CHC in Limpopo. These factors include psychological experiences, social disclosure, behavioural constraints, side effects, etc
Thesis (M. (Nursing)) -- University of Limpopo, 2024
Keywords: Factors; Adherence; Human Deficiency Virus; Patient; Fixed Dose Combination; HIV (Virus); Patient monitoring; Drugs -- Dose-response relationship; Antiretroviral agents